Sensitivity of Non-Performing Assets to GDP and Inflation Rate Volatility - Tabassum; Pande, Sarveshwar (Indian Journal of Finance, 2021)
This research examined the impact of inflation rate and gross domestic product (GDP) and their volatility on the non- performing assets (NPAs) in the Indian scheduled commercial banks from 1996–1997 to 2016–17. It examined how the macroeconomic volatility in the inflation rate and GDP significantly impacted the gross NPAs in the sampled banks. An econometric autoregressive model was employed where the gross NPAs were used as the explained variable, while one-period lags of gross NPAs, GDP, and inflation rate were the regressors. Pearson’s correlation analysis was also employed. Secondary data analysis was done. The findings confirmed that the one-period lag of gross NPAs had a positive and highly statistically significant effect on the gross NPAs ; whereas, GDP and inflation rate had a highly statistically insignificant effect on the gross NPAs in the sampled banks. It is envisaged that future research studies will be accomplished by including bank-specific and other macroeconomic factors. Other categories of Indian banks can be also included in further studies.